2016
DOI: 10.1039/c6dt02948e
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation of a benzyl ligand in SNS-palladium complexes with O2: acceleration by anions or Brønsted acids

Abstract: A cationic SNS-benzylpalladium complex was reacted with O2 under several conditions, affording oxygenated compounds derived from the benzyl ligand. The addition of n-Bu4NX remarkably accelerated the oxygenation, furnishing benzaldehyde as a main organic product and dinuclear complexes; in contrast, HX also promoted the oxygenation, but mainly produced benzyl hydroperoxide and mononuclear complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Prolonging the reaction time of oxygenation to 24 h resulted in the preferential formation of PhCHO (entry 3). The conversion of BnOOH to PhCHO was demonstrated by following the oxygenation by 1 H NMR spectroscopy (Figure ), which is known to be promoted under neutral or basic conditions or in the presence of metal catalysts. , Oxygenation also proceeded in CD 3 CN instead of CDCl 3 , although a slightly higher temperature (50 °C) was required to dissolve 5 ·H 2 O (entry 4). In this reaction, the formation of 4b- d 3 was also observed in 27% yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonging the reaction time of oxygenation to 24 h resulted in the preferential formation of PhCHO (entry 3). The conversion of BnOOH to PhCHO was demonstrated by following the oxygenation by 1 H NMR spectroscopy (Figure ), which is known to be promoted under neutral or basic conditions or in the presence of metal catalysts. , Oxygenation also proceeded in CD 3 CN instead of CDCl 3 , although a slightly higher temperature (50 °C) was required to dissolve 5 ·H 2 O (entry 4). In this reaction, the formation of 4b- d 3 was also observed in 27% yield.…”
Section: Resultsmentioning
confidence: 99%
“…The formed 3 5 readily reacts with 3 O 2 to afford 8 or 9 . The formation of [Pd IV Bn­(MeNNP­(O))­(OOH)] with the assistance of the PA proton and the subsequent reductive elimination or the formation of [Pd II (OOBn)­(MeNNPOH)] via the insertion of O 2 into the Pd–C­(sp 3 ) bond and the subsequent protonolysis of the BnOO ligand by the PA proton affords 8 . The formation of hydrocarbyl hydroperoxo Pd­(IV) or Pt­(IV) complexes by the reaction of hydrocarbyl Pd­(II) or Pt­(II) complexes with O 2 and a proton source is reported or proposed. ,,, On the other hand, the insertion of O 2 into a Pd–Me or Pt–Me bond to form Pd–OOMe or Pt–OOMe complexes is also reported. ,,, The formation of 9 can be explained by a single oxygen atom transfer ,, , from [Pd IV Bn­(MeNNP­(O))­(OOH)] to another PdBn complex 11 to afford two [Pd IV Bn­(MeNNP­(O))­(OH)] and subsequent reductive elimination. Because 5 originally contains a water molecule and water is generated by the decomposition of BnOOH, ligand exchange occurs to form 10 from 8 and 9, along with the release of BnOOH and BnOH.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, single-crystal X-ray analysis could not be performed because the structures could not be obtained as single crystals despite crystallization efforts. A four-coordinated square-plane structure is proposed for Pd(II) complexes [ [65] , [66] , [67] , [68] ].…”
Section: Discussionmentioning
confidence: 99%
“…All the Pd (II) complexes are tetra coordinated, in which the palladium is the coordinated by two acetate groups and N and S donor atoms of the ligands in a square planar geometry. [27][28][29][30][31] Solubility of the complexes was tested, but it was found that the complexes do not dissolve very well in various solvents. NMR spectra of the complexes were taken, but some of them (L1-Pd and L2-Pd) were able to obtain significant spectra, while others (L3-Pd and L4-Pd) could not obtain significant spectra due to poor resolution.…”
Section: Computational Detailsmentioning
confidence: 99%